Trabecular juvenile ossifying fibroma in the mandible: clinical, radiographic and histopathologic features - Alves, Monica Ghislaine Oliveira; Carvalho, Bruna Fernandes do Carmo; Rocha, André Caroli; Ishida, Carlos; Carvalho, Yasmin Rodarte; Almeida, Janete Dias (Journal of Oral Diagnosis, 2017)
Juvenile ossifying fibroma is an uncommon, aggressive, asymptomatic fibro-osseous lesion. An 11-year-old white boy was seen at the stomatology outpatient clinic with a complaint of pain and a one-year history of tooth mobility and extensive swelling in the mandible. Extraoral clinical examination showed major facial asymmetry and swelling in the left mandibular body. Intraoral examination revealed expansion of the buccal and lingual cortical bones. Imaging identified a multilocular mixed lesion in the mandible with hyperdense areas. An incisional biopsy was performed and the combination of clinical, imaging and histopathologic data led to the final diagnosis of juvenile ossifying fibroma. Treatment consisted of segmental mandibulectomy and reconstruction with a microsurgical fibular flap, after 5 years of follow up, no local recurrence was observed. Strategies for the clinical management and treatment of pediatric patient should be designed to offer the best prognosis and quality of life for the patient.